Infantile spasms followed by childhood absence epilepsy: A case series. (January 2020) - Giordano, Lucio; Tambucci, Renato; Cocco, Isabella Emanuela; Angriman, Marco; Coppola, Giangennaro; Operto, Francesca Felicia; Farello, Giovanni; Savasta, Salvatore; Belcastro, Vincenzo; Verrotti, Alberto
Abstract: Purpose: Infantile spasms (IS) represent a severe seizure disorder of infancy and early childhood characterized by epileptic spasms along with hypsarrhythmia often accompanied by intellectual disability. According to the current classification and terminology (3) IS can be categorized as known etiology, formerly known as "symptomatic", when an underlying cause has been observed prior to the onset of spasms, or of "unknown cause" with "unfavorable" and "favorable" outcome (previously referred as "cryptogenic" or "idiopathic", respectively). Single reports described children with "unknown cause and favorable outcome" (UC/FO) IS who later developed childhood absence epilepsy (CAE). This study aims to determine the prevalence of CAE following IS. Methods: a multicenter retrospective chart review was performed; children with UC/FO IS who subsequently developed CAE during follow-up were identified. Eight Italian pediatric epilepsy centers participated in this study. Results: seven out of 24 (29 %) children (3 males) showing a favorable outcome (UC/FO) IS received a second diagnosis of CAE during follow-up. Mean age at IS presentation was 5.8 months (SD ± 0.9). All achieved seizure control of IS at a mean age of 8.5 months (SD ± 1.3) (3 monotherapy, 4 polytherapy). CAE was diagnosed at a mean age of 8.0 years (SD ± 3.0). Six children achieved sustained remission of CAE with valproic acid, whereas 1 child required dual therapy by adding ethosuximide. Conclusion: although it is not possible to determine whether the association between UC/FO IS and CAE implies a causality relationship, the later occurrence of CAE in patients with UC/FO IS might support a possible role of thalamo-cortical dysfunction.